Simulation of Motion Behavior of Concrete in Pump Pipe by DEM - Ji Hao; Caiyun Jin; Yue Li; Zigeng Wang; Jianglin Liu; Hongwen Li (Advances in Civil Engineering)
In this paper, the mesocalibration test was used to measure the contact parameters (restitution coefficient, rolling friction coefficient, static friction coefficient, and surface energy) between coarse aggregate particles and mortar particles in Discrete Element Method (DEM) model of concrete. Then, the DEM model of concrete slump was established according to the coarse aggregate gradation to study the flow behavior of coarse aggregate in fresh concrete. The slump test result was compared with the output of the slump DEM model with high consistent, indicating the promising reliability of the mesocalibration test. Finally, based on the mesocalibration test results, the DEM model of pumping concrete was established. It was obtained that the pumping pressure calculated by the numerical model was similar to that of the pumping test with satisfactory accuracy better than the concrete pumping pressure calculated according to the rheological test results of concrete and lubricating layer. On this basis, the movement trajectory of coarse aggregate in the pump pipe was analyzed and the influence of coarse aggregate on the pumping performance of concrete was revealed.